THE FORMATION OF SPIRITUALITY AND ITS IMPORTANCE IN THE CONSTRUCTION OF CIVIL SOCIETY - Sh. Kholmatov (Journal Park Publishing, 2023)
Spirituality is a concept that represents the human spiritual and mental world. It includes philosophical, legal, scientific, artistic, moral, religious visions of people. On the basis of the term spirituality lies the word "meaning". It is known that a person has an external and internal world. His outer world includes his makeup, appearance, dress, behavior and more. And his inner world includes his purpose, thinking, desires, aspirations, feelings from living. This inner world of man is spirituality. When food gives a person physical strength, spirituality gives him spiritual nourishment and strength. Spirituality is associated with enlightenment and culture. Spirituality does not occur in people with tap-ready. It is achieved only through constant reading, learning, gaining experience. The richer spirituality, the more prosperous society and nation will be.
Keywords: person, society, civil society, spirituality, legal culture, education, family, globalization.